Turning the world upside down : the War of American Independence and the problem of empire - York, Neil Longley (Studies in military history and international affairs., 2003)
York illustrates how Revolutionary Americans founded an empire as well as a nation, and how they saw the two as inseparable. While they had rejected Britain and denounced power politics, they would engage in realpolitik and mimic Britain as they built their empire of liberty. England had become Great Britain as an imperial nation, and Britons believed that their empire promised much to all fortunate enough to be part of it. Colonial Americans shared that belief and sense of pride. But as clashing interests and changing identities put them at odds with the prevailing view in London, dissident c.